Tax strategy disclosure: A greenwashing mandate? - Katarzyna Bilicka; Elisa Casi; Carol Seregni; Barbara M. B. Stage (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
We investigate the effects of a qualitative tax disclosure mandate aimed at improving tax transparency and compliance by imposing reputational costs for firms. We use, as an exogenous shock, the 2016 UK reform that required large businesses to disclose their tax strategy. We find that treated firms-those that must publish a tax strategy report-also significantly increase the volume of tax strategy disclosure in their annual reports but this disclosure contains more boilerplate. The standalone tax strategy reports contain narratives similar to those in the annual reports, are sticky, and their quality is correlated with those of disclosures on gender and human rights. Turning to real behavioral changes, we document no significant effect on tax planning across several proxies and firm characteristics. While we find that the mandate increased media attention on treated firms, our results suggest that this enforcement channel might not work in the context of qualitative disclosure, which may be hard to verify for outside stakeholders. Even in subsamples of firms that we would expect to behave differently, we document similar responses. Taken together, our findings indicate that mandating qualitative tax disclosure has incentivized firms to portray themselves as good tax citizens without changing their practices.
Keywords: G38; M41; M48; H26; H20; 330; Disclosure Regulation; Nonfinancial Disclosure; Corporate Social Responsibility; Tax Transparency; Corporate Tax Avoidance